Pembangunan Model E-Learning di Perguruan Tinggi untuk Meningkatkan Efisiensi Belajar Mengajar - Inayatulloh Inayatulloh (Bina Nusantara University, 2013)
The purpose of this research is to build a model of e-learning for higher education in order to improve the effectiveness of teaching and learning activities. The research method is analyzing the process of learning activities in several universities as a basis for creating a dynamic model of comprehensive e-learning so as to meet the needs of students, lecturers and all parties concerned. In analyzing the teaching-learning process observations at several campuses are conducted to study existing processes and activities. The results are a model of e-learning that can be used by universities in building and developing e-learning applications that already exist.